Risk of subsequent primary leukaemias among 69, 460 five-year survivors of childhood cancer diagnosed from 1940 to 2008 in Europe: A cohort study within PanCareSurFup. (August 2019) - Allodji, Rodrigue S.; Hawkins, Mike M.; Bright, Chloe J.; Fidler-Benaoudia, Miranda M.; Winter, David L.; Alessi, Daniela; Fresneau, Brice; Journy, Neige; Morsellino, Vera; Bárdi, Edit; Bautz, Andrea; Byrne, Julianne; et al.
Abstract: Background: Survivors of childhood cancers are at risk of developing subsequent primary leukaemias (SPLs), but the long-term risks beyond 20 years of treatment are still unclear. We investigated the risk of SPLs in five-year childhood cancer survivors using a large-scale pan-European (PanCareSurFup) cohort and evaluated variations in the risk by cancer and demographic factors. Methods: This largest-ever assembled cohort comprises 69, 460 five-year childhood cancer survivors from 12 European countries. Standardised incidence ratios (SIRs) and absolute excess risks (AERs) were calculated. Results: One hundred fifteen survivors developed an SPL including 86 myeloid leukaemias (subsequent primary myeloid leukaemias [SPMLs]), 17 lymphoid leukaemias and 12 other types of leukaemias; of these SPLs, 31 (27%) occurred beyond 20 years from the first childhood cancer diagnosis. Compared with the general population, childhood cancer survivors had a fourfold increased risk (SIR = 3.7, 95% confidence interval [CI]: 3.1 to 4.5) of developing leukaemia, and eight leukaemias per 100, 000 person-years (AER = 7.5, 95% CI: 6.0 to 9.2) occurred in excess of that expected. The risks remained significantly elevated beyond 20 years from the first primary malignancy (SIR = 2.4, 95% CI: 1.6 to 3.4). Overall, the risk ratio for SPML (SIR = 5.8, 95% CI: 4.6 to 7.1) was higher than that for other SPLs. Conclusions: We demonstrate that beyond 20 years after childhood cancer diagnosis, survivors experience an increased risk for SPLs compared with that expected from the general population. Our findings highlight the need for awareness by survivors and their healthcare providers for potential risk related to SPL. Highlights: The largest-ever assembled cohort of childhood cancer survivors (CCSs) from 12 European countries (PanCareSurFup study). CCSs experience an increased risk for subsequent primary leukaemias compared with that expected from the general population. This risk remained significantly elevated beyond 20 years from the first primary malignancy. The risk for myeloid leukaemias was higher than that for other subsequent primary leukaemias among CCSs.